Populasi, Biomassa dan Jenis Cacing Tanah pada Lahan Sayuran Organik dan Konvensional di Bedugul - ARFITA TRI MAYASARI; ANAK AGUNG ISTRI KESUMADEWI; NI LUH KARTINI (Fakultas Pertanian Universitas Udayana, 2019)
Population, Biomass, and Types of Earthworm on Organic and Conventional Vegetable Land in Bedugul. Earthworm is an important indicator of soil fertility. The type of earthworm closelly associated with soil management system. This research aims to determine the population, biomass, and earthworms type that had been done on organic and conventional vegetable ecosystem in Bedugul from December 2017 until March 2018. The purposive research sites were located in Baturiti Village and Candikuning Village for organic and conventional vegetable systems, respectively. The research area was clustered following Randomized Block Design into three group sites and devided based on organic and conventional system as the first factor. The second factor was soil depth (0-10, 10-20 and 20-30 cm) that nested on cultivation system. Calculation of collected earthworm was done in situ while their morphological identification was done at The Soil Science and Environment Laboratory, Faculty of Agriculture,Udayana University.The results confirmed that earthworm population and biomass were affected by cultivation system but the values were not significantly difference among soil depths. The population and biomass of earthworm found in organic soils were two times higher than those in conventional land. Earthworms population in organic field ranged from 66.67 to 89.33 m-2 and on conventional land ranged from 16.00-45.33 m-2. The weight of earthworm biomass on organic land ranged from 1.00-1.93 g and on conventional land ranged from 0.03-0.06 g. The type of worm acquired on organic soil was Lumbricus terrestris and on conventional land was Pontoscolex corethrurus. We can summary from this research that cultivation systems highly influence the community of earthworm.